2021
DOI: 10.1002/pbc.29547
|View full text |Cite
|
Sign up to set email alerts
|

Six‐month BNT162b2 vaccine efficacy in adolescents and young adults with cancer

Abstract: LETTER TO THE EDITOR experiments and the patients and their family for participation in the study. CONFLICT OF INTERESTCaroline Donze, Laetitia Ninove, and Xavier de Lamballerie have no conflict of interest to disclose. Paul Saultier reports receiving support for attending scientific meetings and educational events from Baxalta-Shire, Novo Nordisk, Pfizer, Octapharma, Roche, Servier, and Sobi and has received honoraria (consultant on advisory boards) from Octapharma outside the area of the submitted work. Nico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…Our results are novel, as data on immune responses on SARS-CoV-2 vaccinations in pediatric immunocompromised patients are scarce, in particular regarding data on the long-term follow-up [4,10,14]. Corroborating our results reported previously [10], one retrospective study reported on good e cacy of SARS-CoV-2 vaccination in 13 patients (median age 17 years) receiving chemotherapy for a solid tumor [14].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Our results are novel, as data on immune responses on SARS-CoV-2 vaccinations in pediatric immunocompromised patients are scarce, in particular regarding data on the long-term follow-up [4,10,14]. Corroborating our results reported previously [10], one retrospective study reported on good e cacy of SARS-CoV-2 vaccination in 13 patients (median age 17 years) receiving chemotherapy for a solid tumor [14].…”
Section: Discussionsupporting
confidence: 67%
“…Corroborating our results reported previously [10], one retrospective study reported on good e cacy of SARS-CoV-2 vaccination in 13 patients (median age 17 years) receiving chemotherapy for a solid tumor [14]. Donze et al evaluated the anti-SARS-CoV-2 immunity in 4, 17 and 17 pediatric cancer patients receiving one, two and three doses of vaccine, respectively, and assessed the humoral, but not the cellular immune response [4]. When they removed the 11 patients with a documented SARS-CoV-2 infection, the probability of maintaining immunity against SARS-Cov-2 in the 15 patients who had responded to vaccination declined to 50% after 259 days post-vaccination [4].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations